Anti-trypanosomal activity of crude root extract of Leptadenia hastata (Pers) decne in Wistar rats infected with Trypanosoma brucei brucei and associated hematological changes - Malgwi, Samson Anjikwi; Zango, Mohammed Kyari; Mbaya, Albert Wulari; Dennis, Gamgong; Kyari, Falmata; Sanda, Kyari Abba; Balami, Stephen Bitrus; Bwala, Abwari David (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: An in vivo study was carried out to evaluate the possible anti-trypanosomal activity of Leptadenia hastata crude root extract with also its associated hematological changes particularly the packed cell volume (PCV) in experimental Trypanosoma brucei brucei infection using Wistar rats. Materials and Methods: Thirty Wistar rats comprising of both males and females were categorized into six separate groups starting from A to F. Wistar placed in Group A and Group B were inoculated with T. brucei brucei and administered crude root extract of L. hastata at 100 and 200 mg/kg, respectively, as the treatment. Group C was infected with the parasite but untreated, while Group D was not infected with the parasite and was not treated. The remaining Groups E and F were inoculated with the parasite using diminazene diaceturate at 3.5 and 7.0 mg/kg, respectively. The extract was administered enterally when parasitemia was detected. Standard laboratory techniques were employed to determine parasitemia and PCV after collection of blood samples every 2 days via the tail vein. Results: Infected Groups (A, B, C, E, and F) showed a pre-patent period 2 days post infection (P.I) with mean parasitic counts of 3.93 ± 2.38, 2.46 ± 2.20, 0.67 ± 0.77, 4.60 ± 4.45, and 1.53 ± 1.44, respectively, which continued unabated in groups treated with the extract.The pack cell volume did not decline significantly in the in Groups A and B. Acute toxicity study revealed the absence of any clinical or behavioral changes suggesting toxicity. Conclusion: There was no effect on parasitemia of Wistar rats infected with the parasite after administration of 100 and 200 mg, respectively, using the extract as the treatment. PCV of the groups infected remained fairly constant with the control groups throughout the study with the extract being non-toxic. J. Adv. Vet. Anim. Res., 6(2): 241-246, June 2019